Voicing the Text, Texting the Voice: Transmediation in a Poetry Reading by Louise Glück - Svensson, Jimmie (Semiotika, 2024)
This article examines the process of transformation from a written poem by Louise Glück to the poet’s oral reading of it, from a semiotic and intermedial perspective. Glück uses Poet Voice, a widespread reading style characterized by a highly stylized prosodic evenness and predictable use of pitch. Whereas an essential trait of traditional metrical verse is its interplay between the artificial, regular meter and a prosodically more natural reading, non-metrical verse such as Glück’s depends on its visual segmentation into lines, often in conflict with syntax. By using Poet Voice, which conflicts with conventional prosody, these essential characteristics of poetry can be transmediated to the oral reading. While this does suppress expressiveness, it helps produce additional meaning in a way specific to poetry, by means of iconicity. The breakthrough of non-metrical verse around 1900 was accompanied by a visual turn; continental theory further contributed to an increased focus on the written text and to skepticism about a traditional lyrical “I.” The second half of the 20th century, however, saw an oral turn, with the poet emerging as the reader or performer of his or her own texts. In this historical context, this oral reading style balances conflicting tendencies by imitating characteristics of the written text: undecidedness, neutrality, and openness to interpretation.